Analisis Efektivitas Penerapan Aplikasi Sistem Keuangan Desa dalam Pengelolaan Keuangan Desa pada Desa Majang Tengah Kabupaten Malang - Faudiana, Lusi; Sodik, M.; Hasan, Khojanah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The Financial and Development Supervisory Agency (BPKP) manages village finances using the siskuedes application system. With this system, the village government can run village finances with good administrative quality for a village. this system aims for the government to run village finances more easily and efficiently in village financial reports. There are also benefits of Siskeudes also supported by the results of research showing that the application of Siskeudes has a very positive impact on time and cost efficiency. this research sample was taken in Majangtengah village, dampit subdistrict. data collection using the text method of interviews with village officials. in this data analysis, researchers processed data from interviews with village officials which the researchers then concluded according to the standards of domestic government regulations NO 20 of 2018. in the study, researchers concluded that the application of the SISKEUDES application in the village was effective and efficient in a transparent and accountable manner.